Optimizing Sharia Insurance in Building Halal Value Chain - Dzukroni, Arisy Abror; Afandi, Mukhamad Yazid (IAIN Kudus, 2022)
The phenomenon of the halal lifestyle demands modern society to fulfill sharia principles in almost all aspects of life. In order to improve the quality of halal integrity to reach the global market potential of US 2.3 trillion, a system is built that can accommodate halal products. In the end, a halal value chain was formed that could integrate various companies and industries to work hand in hand to build a halal ecosystem. One aspect that cannot be abandoned in the development of the halal ecosystem is the financial sector in which transactions and financial mobilization occur. Of course, the system used is Islamic finance, in accordance with the principles of the halal value chain. One of the Islamic finance sectors is sharia insurance. In general, insurance is used as a guarantee if one day there is a loss to the related party. The halal industry certainly does not guarantee the avoidance of business actors from losses. From this, it can be understood that Islamic insurance plays a vital role in developing the halal value chain. Therefore, further research is needed regarding the identification of the role of Islamic insurance in optimizing the halal value chain. This research using qualitative methods and library research aims to analyze the role of sharia insurance in developing the halal value chain. The results found that almost all halal value chain clusters such as food and beverage clusters, halal tourism, fashion, cosmetics, and recreational media require sharia insurance to develop the halal value chain. This is because sharia insurance can guarantee the continuity of sharia-based businesses if there is an unthinkable loss one day. The government needs to pay more attention to implementing the Islamic financial system, one of which is sharia insurance, if it wants to create a halal ecosystem in Indonesia.